The first goblin spiders of the genus Trilacuna from Vietnam (Araneae, Oonopidae) - Tong, Yanfeng; Li, Shuqiang (Zootaxa, 2013)
Two new species of the genus Trilacuna Tong & Li, T. hamata sp. nov. and T. sinuosa sp. nov., are described from Tam Dao National Park, Vietnam.